Towards a Better Understanding of the INTERNIST-1 Knowledge Base - Heckerman, David; Miller, Randolph A. (Proceedings of Medinfo, Washington, 1986)
We consider two probabilistic interpretations for quantities found in the INTERNIST-1 knowledge base called evoking strengths. The first interpretation is based on the definition of evoking strengths while the second is based on the use of evoking strengths in the scoring scheme. We then describe an experiment which can test whether either interpretation is valid. Results of the experiment are presented and discussed. The experiment described in the paper serves as a prototype for the other experiments to better understand the INTERNIST-1 knowledge base.